System integration optimization for coal-fired power plant with CO2 capture by Na2CO3 dry sorbents - Wu, Ying; Chen, Xiaoping; Ma, Jiliang; Wu, Ye; Liu, Daoyin; Xie, Weiyi (Energy (Oxford), 2020)
For the post-combustion CO2 capture by the Na2CO3 dry sorbents, system integration of CO2 capture into an existing coal-fired power plant is of great significance, as the huge energy consumption of CO2 capture results in great efficiency penalty. By system integration optimization, nearly 80% of the low temperature energy released from the CO2 capture could be recovered to gain more power output and provide considerable heat supply for users, yielding a respective 0.6% and 34.13% increment of the net electric efficiency and coal utilization coefficient. Besides, combination with the waste heat recovery of flue gas further increases the net electric efficiency by 0.57%. Both the thermodynamic and exergy analysis results show that the optimization measures provide a promising way for system integration of the coal-fired power plant with CO2 capture. Techno-economic analysis results shows that cost of electricity and cost of CO2 avoided are obviously reduced due to the optimization measures proposed in this paper. •Energy equilibrium of CO2 capture by NA2CO3 solid sorbents is conducted.•Optimization measures are conducted to improve overall performance.•Waste heat recovery is combined with integrated system with CO2 capture.•Thermodynamic, exergy and techno-economic analysis is conducted.